The Effect of Work Motivation & Leadership Style on Working Discipline & Its Impact on Employee Performance in Adhi Karya Ltd, Padang - Allah, Rahmat; ., Heryanto (Archives of Business Research, 2018)
This study aims to determine the effect of work motivation, leadership style on work discipline and its impact on the performance of Adhi Karya Ltd employees. The sample selection was done by sampling purposive with a total sample of 110 employees. Variables in this study consisted of work motivation and leadership styles as independent variables and work discipline as dependent variables, and employee performance as an interverning variable. The data analysis method used in this study is the path analysis method. The results of the study show that 1. Work motivation has a positive and significant influence on work discipline. 2. Leadership style has a positive and insignificant effect on work discipline. 3. Work motivation has a positive and significant effect on employee performance. 4. Leadership style has a positive and not significant effect on employee performance. 5. Work discipline has a positive and not significant effect on employee performance. 6. Work motivation has a positive and significant effect on work discipline and has a positive and not significant impact on employee performance. 7. Leadership style has a positive and insignificant effect on work discipline and has a positive and not significant impact on employee performance.